In situ conservation of forest genetic resources - Vinceti, Barbara; Thomas, Evert (2025)
For FGR, in situ conservation refers to the genetic conservation of tree and other woody plant species in their natural environments by targeting individual populations of these species(FAO, 2014a) with the aim of maintaining or increasing their evolutionary and adaptive potential using natural selection as a driver. In situ conservation is intrinsically dynamic because the populations maintain ecological interactions with other biota and undergo evolutionary processes such as natural selection, genetic drift, and gene flow and mutation (FAO, 2014a).In situ conservation is also the most efficient option for conserving the gene pools of tree species (Kelleher, 2018) because its cost is lowerper unit of genetic diversity than that of ex situ conservation (Gapare, 2013).The in situ conservation of FGR is carried out typically in protected areas and managed forests(FAO, DFSC and IPGRI, 2001) and in forest reserves or stands designated specifically for the genetic conservation of a given species (FAO, 2014a). An important aspect of in situ conservation is that it does not exclude the use of conserved resources. It maintains the ecological, aesthetic, ethical and cultural values of species and simultaneously allows the genetic conservation of multiple species. SoW-FGR1 found that countries interpreted the concept of in situ conservation in different ways and that only about 1 000 species were conserved in situ for their genetic resources (FAO, 2014a). The Global Plan of Action called for the strengthening of in situ FGR conservation and increasing the number of priority species to be targeted for its application (FAO, 2014b). This chapter examines approaches for the in situ conservation of FGR and presents its present state based on country reports. The chapter also reviews recent scientific and technological advances supporting the in situ conservation of FGR in practice. Organizational aspects of in situ conservation are addressed in Chapter 11.